URGENCY OF INTEGRATED ASSESSMENT ON DRUGS CRIME (A Study in Purbalingga Regency) - Saefudin, Yusuf; Raharjo, Agus; Budiono, Budiono (Jurnal Dinamika Hukum, 2017)
Various rules are formulated to repress the drug abuser and trafficking, one of which is through integrated assessment. The paper explains the philosophy of integrated assessment and implementation of the integrated assessment in Purbalingga Regency. This research is empirical by applying methods of survey, observation, interview and literature review. Data were collected and analyzed qualitatively by descriptive analysis. Based on the research result, integrated assessment is a mechanism designed to differentiate drug abusers and addicts from drug traffickers and also to make treatment plan for the drug addicts and drug abusers. In Purbalingga, integrated assessment has been implemented since 2015. Yet practically several obstacles are identified including assessment request and assessment result is overdue issued, lack of coordination among Integrated Assessment Team, secretary facilities of Integrated Assessment Team is not adequate, infrastructure of rehabilitation place is limited and the programs of rehabilitation do not procedurally run.Key words: Integrated Assessment, Drugs Crime, Penal Meditation